Error Analysis Performed by Tour and Travel Business Students as a Tour Guide - Wijaya, Eka Anastasia; Astawa, I Gede (Institut Agama Islam Negeri Palopo, 2024)
Error as an inseparable part of English teaching and learning should be considered as a positive thing, since it could help in improving the teaching and learning process. Therefore, this study was conducted to analyze the error performed by the tour and travel business students in English class in the form of simulation. Framed within a qualitative design, this research used error classification theory by Thornbury. The findings showed that there are 5 lexical errors, 35 grammar errors, and 11 discourse errors performed by the students as a tour guide. It implied that lexical error is the least type of error and grammar error is the major type of error performed by the students. Further, the error performed by the students caused by two major sources. The first source is interference from the native language and the second source is intralingual and developmental factors.